Effects of Apolipoprotein E Isoforms in Diabetic Nephropathy of Chinese Type 2 Diabetic Patients - YongWei Jiang; Liang Ma; ChengWu Han; Qian Liu; Xiao Cong; YaPing Xu; TingTing Zhao; Ping Li; YongTong Cao (Journal of Diabetes Research)
Diabetic nephropathy (DN) is one of the major chronic complications of diabetes. Genetic polymorphism of Apolipoprotein E (ApoE) has been proposed to participating in DN. The purpose of the study was to evaluate the relationship between ApoE genetic polymorphism and the presence of DN in Chinese type 2 diabetic patients. We studied 845 diabetic patients who were divided into DN group (n=429) and control group (n=416). ApoE genotype was determined by ApoE genotyping chip and the plasmatic biochemical characterization was performed on all subjects. There were differences (P<0.001) in HbA1c, creatinine, and urinary albumin between the two groups. The ApoE ε2 allelic frequency was 7.69% in DN group versus 3.49% in control group (OR = 2.22, 95% CI = 1.41–3.47, and P<0.05), as expected, ApoE E2/E2 and E2/E3 genotype frequency were higher in DN group (13.75% versus 6.49%, P<0.05). The ApoE ε4 allelic frequency was 7.93% in DN group versus 11.54% in control group (OR = 0.70, 95% CI = 0.50–0.97, and P<0.05), and DN group presented a lower frequency of ApoE E3/E4 and E4/E4 genotype frequency (14.91% versus 19.96%, P<0.05). These results suggest ApoE ε2 allele may be a risk factor; however ApoE ε4 allele may play a protective role of DN in Chinese type 2 diabetic patients.